Peranan Pasar Modal Dalam Perekonomian Negara di Indonesia - Naila Putri Inayah; Muhammad Haidar Affan; Camelia Oktariani Setiawan; Sihotang Martin Christian (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This study aims to analyze the effect of investment knowledge, capital market training, minimum investment capital and risk perception on student investment interest in the capital market (study at PT Phintraco Sekuritas Branch Office Semarang). This research design is a causal applied quantitative research. The data used are primary data and secondary data. The data collection method used a questionnaire. The sampling technique used was purposive sampling technique, and the sample size was 98 respondents. Instrument trials were analyzed using validity and reliability tests. The data analysis method used is Multiple Linear Regression Analysis. The results of the t test research show that investment knowledge and risk perception have no effect on student investment interest. Capital market training and minimal investment capital affect student investment interest. The results of the F test research show that investment knowledge, capital market training, minimum investment capital and risk perception simultaneously affect student investment interest.